Corporate social responsibility and the parameters of dialogue with vulnerable others - Mayes, Robyn; Pini, Barbara; McDonald, P. (Sage, 2012)
This article presents a case study of corporate dialogue with vulnerable others. Dialogue with marginalized external groups is increasingly presented in the business literature as the key to making corporate social responsibility possible in particular through corporate learning. Corporate public communications at the same time promote community engagement as a core aspect of corporate social responsibility. This article examines the possibilities for and conditions underpinning corporate dialogue with marginalized stakeholders as occurred around the unexpected and sudden closure in January 2009 of the AU$2.2 billion BHP Billiton Ravensthorpe Nickel mine in rural Western Australia. In doing so we draw on John Roberts’ notion of dialogue with vulnerable others, and apply a discourse analysis approach to data spanning corporate public communications and interviews with residents affected by the decision to close the mine. In presenting this case study we contribute to the as yet limited organizational research concerned directly with marginalized stakeholders and argue that corporate social responsibility discourse and vulnerable other dialogue not only affirms the primacy of business interests but also co-opts vulnerable others in the pursuit of these interests. In conclusion we consider case study implications for critical understandings of corporate dialogue with vulnerable others.